Analisis Proses Berpikir Siswa Dalam Menyelesaikan Soal Pada Materi Aljabar - Faturrahman, Faturrahman (Supermat : Jurnal Pendidikan Matematika, 2023)
This research is a qualitative descriptive study that aims to describe students' thinking skills in solving problems on algebra material by class VII students of SMP Muhammadiyah Kota Bima through indicators of analysis, evaluate and create based on the introduction of similar problem structures when students are involved in the investigative process, such as; find patterns, generalize formulas using algebraic symbols and apply formulas to solve problems. The data collection technique was carried out using a question test on 28 students. While the data analysis technique is to reduce and present data and draw conclusions. The results showed that there were 9 high-ability students who met the indicators of analysis, evaluate and create, 15 students who had moderate problem-solving abilities by fulfilling the analysis indicators on differentiating and organizing and did not fulfill the analysis indicators on attributing. Whereas 4 students with low abilities did not meet the analysis indicators on attributing, evaluating on checking and critiquing and creating on generating, planning, and producing, because they only focused on questions and were unable to create new problems, but imitated previous test questions